Does Migration Pay Off in Later Life? Income and Subjective Well-Being of Older Migrants in Europe - Stefan Gruber; Gregor Sand (Social Indicators Research, 2020)
This study examines whether intra-European migration pays off in terms of income and subjective well-being (SWB) for migrants aged 500.167em+0.167emwho are now growing old abroad and in what way their SWB is associated with their relative income position. Using panel data from the Survey of Health, Ageing and Retirement in Europe allows us to go beyond the classical comparison with the native reference group and draw on information about respondents who stayed in the place of origin (`stayers'). Our findings indicate that migration does pay off in later life. Compared to similar stayers, migrants have higher income and higher SWB levels. Furthermore, we find that older migrants' SWB is positively associated with their relative income position for those with an income above the income of both stayers in the origin and natives in the destination country.
Keywords: 300; Migration; Aging; Subjective well-being; CASP; Relative income; SHARE